2023
DOI: 10.1038/s41612-023-00340-3
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented 21st century heat across the Pacific Northwest of North America

Abstract: Extreme summer temperatures are increasingly common across the Northern Hemisphere and inflict severe socioeconomic and biological consequences. In summer 2021, the Pacific Northwest region of North America (PNW) experienced a 2-week-long extreme heatwave, which contributed to record-breaking summer temperatures. Here, we use tree-ring records to show that summer temperatures in 2021, as well as the rate of summertime warming during the last several decades, are unprecedented within the context of the last mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Risk ratios for greater extremes (i.e., HXs and TXs exceeding 2021 daily maximum humidex and air temperature (HXmax and TXmax) show even faster and larger increases (Figures 3c and 3d). The projected change of TX aligns with findings from previous studies that have reported a more frequent occurrence of air temperature extremes surpassing the 2021 level in the WNA region across various future emission scenarios, utilizing different statistical measures including 5‐day temperature anomalies (Dong et al., 2023), maximum daily mean temperature during June–August (Bartusek et al., 2022), and temperature anomalies for June–August (Heeter et al., 2023). However, CanESM5 generally has difficulty simulating extreme dry humidex values (i.e., those that coincide with drier than average conditions, as in the 2021 event) in the current climate (Figure 3e).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Risk ratios for greater extremes (i.e., HXs and TXs exceeding 2021 daily maximum humidex and air temperature (HXmax and TXmax) show even faster and larger increases (Figures 3c and 3d). The projected change of TX aligns with findings from previous studies that have reported a more frequent occurrence of air temperature extremes surpassing the 2021 level in the WNA region across various future emission scenarios, utilizing different statistical measures including 5‐day temperature anomalies (Dong et al., 2023), maximum daily mean temperature during June–August (Bartusek et al., 2022), and temperature anomalies for June–August (Heeter et al., 2023). However, CanESM5 generally has difficulty simulating extreme dry humidex values (i.e., those that coincide with drier than average conditions, as in the 2021 event) in the current climate (Figure 3e).…”
Section: Resultssupporting
confidence: 84%
“…The WNA heatwave region includes parts of the western and central provinces and territories of Canada, as well as Washington and portions of the northwestern states in the US. This region largely overlaps with the area used in previous studies, which have mainly been defined based on extreme temperatures during the 2021 heatwave event (e.g., Dong et al., 2023; Heeter et al., 2023; Lin et al., 2022; Qian et al., 2022; Thompson et al., 2022; White et al., 2023). The HX95 anomaly in the summer of 2021 was approximately +5.40°C higher than the average of 1951–1980 (Figure 1b).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We neglect the carbonplan ensembles here since they contain a limited number of models. which has been extensively studied after breaking several temperature records throughout the region [39][40][41][42], leading to widespread impacts across many sectors [43]. During this event, Seattle-Tacoma airport recorded a temperature of 42.2 • C [44].…”
Section: Implications For Risk Assessmentmentioning
confidence: 99%
“…Consider three recent notable heat events in the Northern Hemisphere: the June 2021 heat wave over the Pacific Northwest (e.g., Bartusek et al., 2022; Bercos‐Hickey et al., 2022; Emerton et al., 2022; Heeter et al., 2023; Loikith & Kalashnikov, 2023; McKinnon & Simpson, 2022; Philip et al., 2022; Schumacher et al., 2022; Thompson et al., 2022; White et al., 2023), the July 2022 heat wave over the United Kingdom and Western Europe (e.g., Holley & Lee, 2022; Yule et al., 2023), and the July 2023 heatwave centered over the Mediterranean (https://climate.copernicus.eu/european-heatwave-july-2023-longer-term-context). From a local perspective, the likelihood of such events is very small: the return time of the 2021 Pacific Northwest heat wave has been estimated as anywhere from once in 200 years to once in 100,000 years (Bartusek et al., 2022; McKinnon & Simpson, 2022; Philip et al., 2022; White et al., 2023).…”
Section: Introductionmentioning
confidence: 99%